2001
DOI: 10.1097/00006534-200106000-00013
|View full text |Cite
|
Sign up to set email alerts
|

The Adductor Flap: A New Method for Transferring Posterior and Medial Thigh Skin

Abstract: Skin flaps from the medial aspect of the thigh have traditionally been based on the gracilis musculocutaneous unit. This article presents anatomic studies and clinical experience with a new flap from the medial and posterior aspects of the thigh based on the proximal musculocutaneous perforator of the adductor magnus muscle and its venae comitantes. This cutaneous artery represents the termination of the first medial branch of the profunda femoris artery and is consistently large enough in caliber to support m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 9 publications
3
69
0
4
Order By: Relevance
“…17,18 A large flap encompassing almost the entire posterior thigh can survive on this single perforator. 15 In the obese individual, identification of the exact location of this perforator can be difficult, but is simplified by a subfascial approach. If designed as a propeller flap with the perforator as the hub, the adductor muscle perforator flap can be rotated to close either an ischial or trochanteric defect and allow simultaneous direct closure of the donor site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 A large flap encompassing almost the entire posterior thigh can survive on this single perforator. 15 In the obese individual, identification of the exact location of this perforator can be difficult, but is simplified by a subfascial approach. If designed as a propeller flap with the perforator as the hub, the adductor muscle perforator flap can be rotated to close either an ischial or trochanteric defect and allow simultaneous direct closure of the donor site.…”
Section: Discussionmentioning
confidence: 99%
“…These used specifically for pressure sores have previously included flaps based on musculocutaneous perforators from the superior 12 and inferior gluteal artery, 13 as well as the first perforator of the profunda femoris artery. 14 Angrigiani et al 15 have also identified a constant, large perforator of the medial posterior thigh arising through the adductor magnus muscle. This can support almost the entire posterior thigh skin territory and was used by them to raise a large thigh flap that could be advanced cephalad for ischial defects, but a skin graft was invariably necessary to close the distal thigh donor site.…”
mentioning
confidence: 99%
“…Hurwitz described the use of a posterior thigh myocutaneous flap based on the inferior gluteal artery, 4 Angrigiani et al described the transfer of posterior and medial thigh skin based on profunda femoris perforators, 5 and Song et al discussed the use of the posterior thigh perforator free flap. 6 Cadaver studies have shown that the dominant blood supply to the posterior thigh is from the profunda femoris artery perforators.…”
mentioning
confidence: 99%
“…El pedículo es siempre posterior al borde posterior del músculo recto interno, del semimembranoso y del semitendinoso (Fig.1). Una vez localizado el eje vascular se termina la disección levantando el borde anterior del colgajo, lo que permite su rotación (3,4) (Fig. 2).…”
Section: Técnica Quirúrgicaunclassified